2017
DOI: 10.1016/j.stemcr.2016.11.012
|View full text |Cite
|
Sign up to set email alerts
|

Primary Human Testicular Cells Self-Organize into Organoids with Testicular Properties

Abstract: SummarySo far, successful de novo formation of testicular tissue followed by complete spermatogenesis in vitro has been achieved only in rodents. Our findings reveal that primary human testicular cells are able to self-organize into human testicular organoids (TOs), i.e., multi-cellular tissue surrogates, either with or without support of a biological scaffold. Despite lacking testis-specific topography, these mini-tissues harbored spermatogonia and their important niche cells, which retained specific function… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
113
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 128 publications
(114 citation statements)
references
References 27 publications
0
113
0
1
Order By: Relevance
“…Organoid systems are becoming popular in vitro models of organ development (Fatehullah et al 2016). Isolated preparations of human somatic and germ cells can selforganize into a testicular-like organoid using an artificial scaffold to aid 3D organization (Baert et al 2017). These studies make use of cells that have already undergone sex-specific differentiation, as the cells are isolated from post-natal tissues (Baert et al 2017).…”
Section: Future Directions: Unravelling the Molecular Pathways Of Earmentioning
confidence: 99%
See 1 more Smart Citation
“…Organoid systems are becoming popular in vitro models of organ development (Fatehullah et al 2016). Isolated preparations of human somatic and germ cells can selforganize into a testicular-like organoid using an artificial scaffold to aid 3D organization (Baert et al 2017). These studies make use of cells that have already undergone sex-specific differentiation, as the cells are isolated from post-natal tissues (Baert et al 2017).…”
Section: Future Directions: Unravelling the Molecular Pathways Of Earmentioning
confidence: 99%
“…Isolated preparations of human somatic and germ cells can selforganize into a testicular-like organoid using an artificial scaffold to aid 3D organization (Baert et al 2017). These studies make use of cells that have already undergone sex-specific differentiation, as the cells are isolated from post-natal tissues (Baert et al 2017). Recently, Sepponen et al, reported using human embryonic stem cells (hESCs) culture conditions to sequentially induce the primitive streak, followed by intermediate mesoderm and finally bi-potential-like gonadal cells expressing genes such as LHX9, EMX2, WT1 and GATA4 (Sepponen et al 2017).…”
Section: Future Directions: Unravelling the Molecular Pathways Of Earmentioning
confidence: 99%
“…Spermatogonial kök hücrelerin (SSCs) nişi; çoğalması ve farklılaşması yönünde halen bilinmeyen birçok faktör vardır. Testiküler organoidler bizlere, bu mekanizmaların aydınlatılması için fırsatlar sunabilir (38)(39)(40)(41)(42).…”
Section: Nonobstrüktif Azospermi Etyolojisi Ve Tedavi Seçenekleriunclassified
“…Organoid and organ-on-a-chip technologies are suitable replacement for animal models and will potentially impart multicellular in vitro organoid-related information on mechanisms of human toxicity and disease etiology. Organoids have been made from primary cell cultures, differentiated embryonic stem cells, or differentiated induced pluripotent stem cells (iPSC) for the liver (Cao et al, 2017 ), the heart (Beauchamp et al, 2015 ; Conant et al, 2017 ; Devarasetty et al, 2017 ), the brain (Hunsberger et al, 2015 ; Schwartz et al, 2015 ), the kidney (Astashkina et al, 2012 ; Chuah and Zink, 2017 ), the testes (Baert et al, 2017 ), the bladder (Janssen et al, 2013 ), and potentially multiple other organs and tissues (Xinaris et al, 2015 ; Ingersoll et al, 2016 ; Skardal et al, 2016 ). Liver toxicity, indicated by liver cell death (Weber et al, 2016 ; Wong et al, 2016 ), and cardiac toxicity, indicated by changes in heart beat kinetics (Meattini et al, 2017 ; Yu et al, 2017 ), account for most drug candidate failures in human trials.…”
Section: Organoid Toxicology Using Primary Cells and Human Embryonic mentioning
confidence: 99%